Sistem Informasi Change Request Form (SI-CRF) dengan Metode V-Model - Rufiyadi, Slamet; Yusnaeni, Wina; Basri, Hasan (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System, 2023)
PT ADM is one of the companies incorporated in the Astra Group, Astra Industries Business unit and is the sole agent of Daihatsu. One of the activities in it is submission which is better known as Change Request Form (CRF). CRF one of the forms used for submission, ID requests related to requests related to IT software such as access rights, licenses, or network installation. submission of Change Request Form (CRF) from the side of Users (in this case as a requester) have difficulty both when filling out documents, approval requests to related superiors, and especially in tracking the status of the request already at what stage , as well as archival document storage because it is still input manually. Based on this explanation, the design of Information System is built using V-model method where V-Model development of waterfall method. Information system built CRF information system that can help users can submit anywhere and in terms of checking can be up to date, in terms of approval and assignment and status can also be checked up to date